Avaliação limnológica da lagoa central (Município de Lagoa Santa - MG): uma abordagem espacial - Ludmila Silva Brighenti (2009)
The concern about the decrease of ecological health of freshwater resources has been increasing dramatically in recent years. Therefore, there is a huge demand of finding new technologies aimed at the recovery and conservation of freshwater resources specially in the tropical belt. Accordingly, the application of new technologies such as GIS (Geographic Information System), automated sensors and hydroacoustics tools is very promising. This project was developed in the Lagoa Central lake (Lagoa Santa, MG, Brazil) in the metropolitan area of Belo Horizonte and it has the following objectives: 1. perform the morphometric and limnological characteristics of Lagoa Central, 2. develop an intensive limnological survey with special emphasis on horizontal patterns; 3. assess the feasibility of applying the technique of single target analysis and echo integration in the study of fish stocks; 4. generate data that can contribute to the development of a management, control and mitigation of eutrophication and the recovery of the lake ichthyofauna. The morphometric characterization was performed by comparing two protocols used for obtain a bathymetric chart and the estimation of morphometric parameters of primary and secondary environment. The tested tools were the echosounder Biosonics DT-X (Biosonics Inc.) and the echobathymetry SonarLite (Ohmnex Ltda), both coupled to a Differential Global Positioning System (DGPS) to acquire the geographic coordinates associated with the depth in each point. The echosounder Biosonics DT-X was also used to study the distribution, density and size structure of echoes associated with fish in the pond. The limnological characterization of the ecosystem was studied with emphasis on the horizontal variation of the parameters of water quality. The study of longitudinal variation of limnological parameters showed that the lake does not present clear and common standards for the physical-chemical variables analyzed. But have inferred the presence of two possible points of entry of allochthonous material, north and southeast ends of the lagoon. The correlations between abiotic parameters and the variation of the density of echoes associated with fish were not relevant and suggested that the spatial distribution of these organisms is influenced by other factors. The Lagoa Central is a small natural lake, shallow (Zmax <7.5 m) with low relative depth (Zr = 0.5%) and concave shape. The hydroacoustics survey showed that the average density found was 0,89 echo associated with fish per m2, indicating large variations in the density of fish in particular areas of the lake. The size estimated for the echoes associated with fish range from 2.7 to 15.9 cm (mean = 5.3 cm). Keywords: bathymetry, biosonics, echobatymetry, hydroacoustics, spatial